HOW PERCEIVED RISK AND TRUST AFFECT ONLINE PAYMENT INTENTIONS: A SURVEY-BASED STUDY WITH CONFIRMATORY FACTOR ANALYSIS (CFA) AND STRUCTURAL EQUATION MODELLING (SEM) - Rahul R. Verma (Asia Information System Journal, 2025)
The rapid expansion of digital financial services has transformed transaction behaviors, yet understanding the specific drivers of purchase intention remains complex. Comprehensive literature reviews exist, there is a lack of empirical research that distinctly separates "online purchase intention" from general "purchase intention," particularly regarding how specific risk dimensions directly erode user trust in emerging platforms. This study aims to bridge this gap by empirically examining the structural relationships between perceived risk (financial, privacy, and performance), trust, and online purchase intention. A quantitative survey approach was employed, gathering data from 300 respondents. The measurement model and structural paths were validated using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM). The findings reveal that perceived risk significantly negatively affects trust. However, trust demonstrates the strongest positive effect on intention (β=0.53), accounting for substantial variance (R 2=0.52) in the model. These results suggest that fintech providers must prioritize trust-building mechanisms over merely functional features. Future research is recommended to explore moderating factors such as user experience levels to further validate this model across different demographics